2018
DOI: 10.1021/acssynbio.7b00413
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Orthogonal Molecules Using Ferredoxin and Ferredoxin-NADP+ Reductase Systems Enables Genetically Encoded PhyB Optogenetics

Abstract: Transplanting metabolic reactions from one species into another has many uses as a research tool with applications ranging from optogenetics to crop production. Ferredoxin (Fd), the enzyme that most often supplies electrons to these reactions, is often overlooked when transplanting enzymes from one species to another because most cells already contain endogenous Fd. However, we have shown that the production of chromophores used in Phytochrome B (PhyB) optogenetics is greatly enhanced in mammalian cells by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…For example, although PCB is not naturally produced in nonphotosynthetic species, BV is widely distributed in nature including yeast and mammals. For this reason, biosynthesis of PCB has also been engineered into eukaryotic "chassis" organisms that naturally do not produce these compounds (75)(76)(77)(78). Increased expression of heme oxygenases has been used to enhance the Cyanobacterial photoactivatable adenylyl cyclases synthesis of BV in bacterial and mammalian cells (79,80).…”
Section: Applications Beyond Photosynthetic Speciesmentioning
confidence: 99%
“…For example, although PCB is not naturally produced in nonphotosynthetic species, BV is widely distributed in nature including yeast and mammals. For this reason, biosynthesis of PCB has also been engineered into eukaryotic "chassis" organisms that naturally do not produce these compounds (75)(76)(77)(78). Increased expression of heme oxygenases has been used to enhance the Cyanobacterial photoactivatable adenylyl cyclases synthesis of BV in bacterial and mammalian cells (79,80).…”
Section: Applications Beyond Photosynthetic Speciesmentioning
confidence: 99%
“…Another potential issue is that the supplemented PCB may not reach proper concentrations in certain tissues in vivo , which may affect the potency of PhotoGal4. However, it has been shown that mammalian cultured cells expressing cyanobacterial enzymes PcyA and HO1 can successfully transform endogenous heme groups into PCB ( Kyriakakis et al., 2018 ; Muller et al., 2013b ; Uda et al., 2017 ; Youichi Uda et al., 2020 ). We strongly believe that genetic synthesis of PCB will pave the way for more practical applications of PhotoGal4.…”
Section: Discussionmentioning
confidence: 99%
“…These four genes were engineered to synthesize PCB at sufficient concentrations in the mitochondria to drive detectable PhyB-PIF activation ( Uda et al, 2017 ). Moreover, with a similar approach, Kyriakakis et al (2018) observed that variation in rate of expression of HO1-PcyA versus Fd-FNR in mammalian cells has a direct correlation with the production levels of PCB in mitochondria, which is further limited on the cytoplasm by heme restriction. A complementary approach proposed reducing the metabolism of biliverdin by knocking down or knocking out the biliverdin reductase A, a mammalian endogenous PCB metabolic agent, resulting, therefore, in an increase of available PCB ( Uda et al, 2017 ).…”
Section: A Photon Of Optionsmentioning
confidence: 92%